Evaluation of functional outcome of lumbar spondylolisthesis treated with posterior lumbar interbody fusion with instrumentation - Raja, K. S.; Ravi, M. (International Journal of Research in Orthopaedics, 2018)
Background: Spondylolisthesis with or without spondylolysis occurs in 5% to 8% of the adult population. It is commonly believed that spondylolysis does not exist at birth. The incidence is 4.4% to 5% at the age of 6 years, increasing to 6% at the age of 18 years, which is quite similar to that observed in adulthood.To analyze the functional outcome of posterior stabilization by pedicle screws with decompression and interbody fusion by PLIF (Posterior Lumbar Interbody Fusion) technique in adult single level spondylolisthesis. In this study our aim is to analyze the correlation between the degrees of fusion with functional outcomes. Methods: This is a prospective study of 20 patients carried out in the Department of Orthopaedics, Govt. Dharmapuri Medical College Hospital, Dharmapuri from January 2016 to December 2017. All patients were evaluated with anteroposterior, lateral and oblique radiographs of the lumbosacral spine. Dynamic plain radiographs of all our patients showed instability. CT/MRI evaluation of all patients was done. Results: In our study four patients (20%) had a complete reduction of the preoperative slip, fourteen patients (70%) showed a reduction of slip by one grade, while in two patients (10%) there was no change from the preoperative slip percentage. Conclusions: Further, three dimensional multislice thin section CT scans with multiplanar reconstruction are ideal to study the incorporation of the bone graft within the disc space.